Introduction - Peter King (Play Across Childhood, 2022)
This chapter introduces the concept of Brofenbrenner’s (The Ecology of Human Development: Experiments by Nature and Design. Harvard University Press, 1979) Ecological Systems Theory (EST) and how it can be considered in the context of children’s play. Outlining the contributions from around the world, play is considered where it takes place within the play provision, and other factors which will influence how children play, such as theory, practice, policy and legislation, are reflected in the contributors’ chapters.